2020
DOI: 10.1002/adsc.202001018
|View full text |Cite
|
Sign up to set email alerts
|

β‐Trifluoromethyl α,β‐unsaturated Ketones: Efficient Building Blocks for Diverse Trifluoromethylated Molecules

Abstract: The trifluoromethyl (CF 3) group is an advantageous structural motif in various biologically active molecules as well as materials, which is depicted by steadily increasing demand from the industries involved in drug discovery, agrochemicals and material development. β-trifluoromethyl α,βunsaturated carbonyl compounds constitute a very efficient building blocks as starting material in the synthesis of fluorinated molecules. Their usage for the synthesis of various heterocycles and organic molecules bearing ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 164 publications
(170 reference statements)
0
31
0
Order By: Relevance
“…Thus recently, efforts from the scientific community have resulted in the design of several elegant and efficient methods to synthesize diverse organofluorine scaffolds using fluorinated building blocks. [38][39][40][41][42][43][44] Moreover, C-H functionalization via C-H activation under transition-metal catalysis [45][46][47][48] has tremendously gained a lot of attention in the recent past as it has the potential to transform an unreactive C-H bond ubiquitously present in all organic molecules. In particular, directing group assisted C-H activation has enabled the synthesis of complex molecular frameworks including various C-C and C-heteroatom connections.…”
Section: Akshay Kamblementioning
confidence: 99%
See 2 more Smart Citations
“…Thus recently, efforts from the scientific community have resulted in the design of several elegant and efficient methods to synthesize diverse organofluorine scaffolds using fluorinated building blocks. [38][39][40][41][42][43][44] Moreover, C-H functionalization via C-H activation under transition-metal catalysis [45][46][47][48] has tremendously gained a lot of attention in the recent past as it has the potential to transform an unreactive C-H bond ubiquitously present in all organic molecules. In particular, directing group assisted C-H activation has enabled the synthesis of complex molecular frameworks including various C-C and C-heteroatom connections.…”
Section: Akshay Kamblementioning
confidence: 99%
“…experiments revealed that the LUMO energy level of the fluorinated α,β-unsaturated carbonyl compound was lower than that of the non-fluorinated one which indicates the feasibility for higher reactivity of these fluorinated building blocks. [196][197][198][199] To this end, for the first time, Yu et al, in 2016, showed the conjugate addition of β-CF 3 enone 283 with arenes under Rh(III) catalysis and redox neutral conditions. Pyridine 282 as a directing group was used for the reaction to obtain the conjugated trifluoromethyl alkylated compounds 284 in good to high yields as shown in Scheme 52.…”
Section: Ethylbromodifluoroacetate As a Building Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Enones have exhibited high activity in C–H activation chemistry, and CF 3 -substituted enones are particularly reactive and have been widely used in transition-metal-catalyzed coupling reactions, affording diverse cyclic or noncyclic skeletons. This class of substrate can readily undergo insertion. The cascade addition process together with other transformations can lead to cyclic and spirocyclic products .…”
mentioning
confidence: 99%
“…However, these Stetter reactions limited to the generation and transformation of stabilized carbanion intermediates. In sharp contrast, unstable carbanion intermediates, such as the highly unstable trifluoromethyl carbanion intermediates, involved Stetter reactions that have never been reported, which might become a direct route to access useful β-trifluoromethylated ketones …”
mentioning
confidence: 99%